A new energy balance-based method for evaluating seismic performance of isolated bridges under near-fault ground motions. (December 2021) - He, Zhongying; Yang, Heng; Zhu, Jinyong; Pang, Yutao
Abstract: This paper aims to evaluate the seismic performance of isolated bridges under near-fault ground motions based on Energy Balance Method (EBM). This method invokes the concept of energy balance into the modal pushover analysis to assess the nonlinear behavior of lead rubber bearings on bridge piers. In EBM, the energy-based capacity curve is firstly obtained by the pushover analysis, while the demand curve is estimated based on the synthetic near-fault record. The target performance criterion can be derived by intersecting the capacity curve with the demand curve. The present paper also proposes the design method for seismic isolation based on the concept of EBM. The case study of an example isolated bridge at a near-fault site is used to illustrate the effectiveness and accuracy of the EBM. The results from this method are evaluated and compared with those from the nonlinear time-history analysis. Results show that the energy-based EBM is found to be able to evaluate the seismic performance of the pier isolated with lead rubber bearings under near-fault ground motions, which can be used as an effective alternative for rapid assess the seismic performance of isolated bridges The results also indicate that the EBM cannot only effectively evaluate the seismic responses of isolated bridges, but also can effectively estimation of the effect of isolation bearing in reducing the displacement and damage of piers.